Предмет: Алгебра,
автор: chirkovalex210710
Спростіть вираз: - a) 2a - (3b - a) + (3b - 2a); б) 6(а - 2) - 3(2a - 5).
Ответы
Автор ответа:
0
а) 2a - (3b - a) + (3b - 2a) = 2a - 3b + a + 3b - 2a = 2a - 2a + a - 3b +`3b = 0 + a - 0 = a
б) 6(a - 2) - 3(2a - 5) = 6a - 12 - 6a + 15 = - 12 + 15 = 6a - 6a - 12 + 15 = 0 - 12 + 15 = 3
Объяснение: .
Похожие вопросы
Предмет: Математика,
автор: Kotik202311
Предмет: Українська мова,
автор: danildana244
Предмет: Математика,
автор: masha5374
Предмет: Қазақ тiлi,
автор: lanalorents1